Pengaruh Green Marketing dan Brand Image Terhadap Keputusan Pembelian Produk Susu UHT Ultra Milk di Kecamatan Pameungpeuk Kabupaten Bandung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research was conducted on consumers of Ultra Milk UHT milk in Pameungpeuk District, Bandung Regency. The focus of this study is to determine the influence of green marketing and brand image on purchasing decisions, both gradually and partially. This study will use descriptive and associative methods. In this study, the unit of analysis is the individual, namely consumers of Ultra Milk UHT milk in Pameungpeuk District, Bandung Regency. The sample in this study was 150 respondents. Sampling was collected using certain considerations or criteria. The sampling method used in this study was multiple linear regression analysis. In addition, the validity and reliability of the research instrument based on research findings showed that variables were partially and simultaneously influenced by green marketing and brand image on the dependent variable (purchase decisions). The influence of green marketing on purchasing decisions was 24.62%, while the influence of brand image on purchasing decisions was 59%. The influence of green marketing and brand image on purchasing decisions was 83.8%.